A formação em nível superior dos assentados de reforma agrária no Curso de Geografia (UFPA/PRONERA): avaliação - Viegas, Renata do Socorro Lima (2022)
It evaluates the training of graduates of the Geography Course, offered through the partnership between UFPA/INCRA/PRONERA, as well as measures their contribution to the socio-spatial development of the Agrarian Reform settlements where they live. For this purpose, a historical assessment of Brazilian higher education was carried out, as well as the struggle for land and for an education with methodological assumptions for the specificity of the field. The relevance of PRONERA for strengthening the education of rural populations is evidenced, aiming at the creation of social protagonism, with support in the local population, expanding the possibility of socio-territorial intervention in the countryside, especially in peasant loci in the Amazon. For the analysis of the object of study proposed here, it is considered necessary to understand the theoretical categories related to it, namely, Rural Education, Agrarian Reform and Public Policies. In this way, we chose to use a reference made up of authors who approach the theme, given the importance of understanding it in a critical-dialectical perspective, which requires a socio-historical analysis of the social, political and economic determinants that involve the matter under examination. The methodological subsidies for the approach consist of carrying out a descriptive study, of a qualitative and quantitative nature, with a methodological design based on the case study.